Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity and ACE Inhibitory Peptides of Salmon (Salmo salar) Protein Hydrolysates Obtained by Human and Porcine Gastrointestinal Enzymes - Darewicz, Małgorzata (MDPI, 2014)
The objectives of the present study were two-fold: first, to detect whether salmon protein fractions possess angiotensin I-converting enzyme (ACE) inhibitory properties and whether salmon proteins can release ACE inhibitory peptides during a sequential in vitro hydrolysis (with commercial porcine enzymes) and ex vivo digestion (with human gastrointestinal enzymes). Secondly, to evaluate the ACE inhibitory activity of generated hydrolysates. A two-step ex vivo and in vitro model digestion was performed to simulate the human digestion process. Salmon proteins were degraded more efficiently by porcine enzymes than by human gastrointestinal juices and sarcoplasmic proteins were digested/hydrolyzed more easily than myofibrillar proteins. The ex vivo digested myofibrillar and sarcoplasmic duodenal samples showed IC(50) values (concentration required to decrease the ACE activity by 50%) of 1.06 and 2.16 mg/mL, respectively. The in vitro hydrolyzed myofibrillar and sarcoplasmic samples showed IC(50) values of 0.91 and 1.04 mg/mL, respectively. Based on the results of in silico studies, it was possible to identify 9 peptides of the ex vivo hydrolysates and 7 peptides of the in vitro hydrolysates of salmon proteins of 11 selected peptides. In both types of salmon hydrolysates, ACE-inhibitory peptides IW, IY, TVY and VW were identified. In the in vitro salmon protein hydrolysates an ACE-inhibitory peptides VPW and VY were also detected, while ACE-inhibitory peptides ALPHA, IVY and IWHHT were identified in the hydrolysates generated with ex vivo digestion. In our studies, we documented ACE inhibitory in vitro effects of salmon protein hydrolysates obtained by human and as well as porcine gastrointestinal enzymes.